2022
DOI: 10.1002/hyp.14743
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying subsurface parameter and transport uncertainty using surrogate modelling and environmental tracers

Abstract: We combine physics‐based groundwater reactive transport modelling with machine‐learning techniques to quantify hydrogeological model and solute transport predictive uncertainties. We train an artificial neural network (ANN) on a dataset of groundwater hydraulic heads and 3H concentrations generated using a high‐fidelity groundwater reactive transport model. Using the trained ANN as a surrogate model to reproduce the input–output response of the high‐fidelity reactive transport model, we quantify the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In recent years, several surrogate model approaches have been suggested to approximate simulation models for uncertainty analysis, such as Polynomial Chaos Expansion (PCE); Gaussian Process Emulation (GPE) [41]; Gaussian processes [42]; Kriging [26,43,44]; Radial Basis Function (RBF) [45]; Support Vector Regression (SVR) [46]; Artificial Neural Network (ANN) [47]; Multi-gene Genetic programming (MGGP) [48]; Kernel Extreme Learning Machine (KELM) [49]; a hybrid approach using the Multilevel Monte Carlo method (MLMC); a graph convolutional neural network and a feed-forward neural network [50]; and a Deep Belief Neural Network (DBNN) [51]. While earlier studies have demonstrated certain achievements, the application of surrogate models encounters challenges related to scalability and accuracy, particularly in scenarios where contaminantrelated associations exhibits pronounced non-linearity or high dimensionality [52].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several surrogate model approaches have been suggested to approximate simulation models for uncertainty analysis, such as Polynomial Chaos Expansion (PCE); Gaussian Process Emulation (GPE) [41]; Gaussian processes [42]; Kriging [26,43,44]; Radial Basis Function (RBF) [45]; Support Vector Regression (SVR) [46]; Artificial Neural Network (ANN) [47]; Multi-gene Genetic programming (MGGP) [48]; Kernel Extreme Learning Machine (KELM) [49]; a hybrid approach using the Multilevel Monte Carlo method (MLMC); a graph convolutional neural network and a feed-forward neural network [50]; and a Deep Belief Neural Network (DBNN) [51]. While earlier studies have demonstrated certain achievements, the application of surrogate models encounters challenges related to scalability and accuracy, particularly in scenarios where contaminantrelated associations exhibits pronounced non-linearity or high dimensionality [52].…”
Section: Introductionmentioning
confidence: 99%
“…Using physically‐based models to inform machine learning methods can overcome these limitations and create opportunities for the development of new research frameworks. Thiros et al (2022) use these ideas to solve a classic model parameterization problem. The authors trained a deep learning model with outputs from a computationally‐heavy distributed transport model, in effect generating a machine surrogate.…”
mentioning
confidence: 99%